2022
DOI: 10.1103/physreva.106.032421
|View full text |Cite
|
Sign up to set email alerts
|

Multipartite subspaces containing no locally inaccessible information

Abstract: One notion of non-locality in quantum theory is the fact that information may be encoded in a composite system in such a way that it is not accessible through local measurements, even with the assistance of classical communication. Thus, contrary to the classical case, there exists information in quantum many body systems which cannot be accessed locally. We show however that, remarkably, two-dimensional subspaces do not have this property: any physically allowed measurement on information encoded in any two-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Even in quantum foundations, non-locality may refer to different properties. For example, entanglement itself is sometimes considered non-local despite being locally created [35]. The latter in particular has created a lot of confusion, because while it has been experimentally shown that entanglement is a non-local correlation and does in fact exist, this does not imply that nature is non-local in the sense that the term has been used in Bell’s theorem, which has of course not been shown [36].…”
Section: General Model Propertiesmentioning
confidence: 99%
“…Even in quantum foundations, non-locality may refer to different properties. For example, entanglement itself is sometimes considered non-local despite being locally created [35]. The latter in particular has created a lot of confusion, because while it has been experimentally shown that entanglement is a non-local correlation and does in fact exist, this does not imply that nature is non-local in the sense that the term has been used in Bell’s theorem, which has of course not been shown [36].…”
Section: General Model Propertiesmentioning
confidence: 99%